Gender and sexuality in the workplace - Williams, Christine L., 1959-; Dellinger, Kirsten (Research in the sociology of work ;, 2010)
This volume features sociological research and theory on gender and sexuality in the workplace, and identifies how organizations can achieve a gender-balanced and sexually-diverse work force. While identifying characteristics of work organizations that have made important strides to achieving equality in the workplace, articles also detail how women and sexual minorities continue to face discrimination, harassment, and exclusion. Special attention is paid to how race and class shape the experience of discrimination for these groups. Topics discussed are wide-ranging and include: gender discrimination and the wage gap; sexual minorities (LGBT workers); homophobic and 'gay friendly' workplaces; sexual harassment; sex in the workplace; sex work and sex workers; gender equity policies; transgender workers; men and women in non-traditional jobs; occupational gender segregation; and, gender difference in work hours. "The Research in the Sociology of Work" series is proud to publish the works of new and established scholars on these important topics, including both quantitative and qualitative studies, as well as review essays that set the agenda for future sociological analysis.